Failure to demonstrate specificity of the morphological and histochemical changes in mucosa adjacent to colonic carcinoma (transitional mucosa). Issue 3 (March 1979) - Isaacson, P; Attwood, P R
Abstract : Characteristic morphological and histochemical changes in mucosa adjacent to colorectal adenocarcinomas have been described. It has been suggested that this type of mucosa, labelled transitional mucosa (TM) because of its specific association with colorectal adenocarcinoma, is indicative of a premalignant change. In an investigation of mucosa adjacent to anal tumours extending into the rectum and mucosa from solitary ulcer syndrome and colostomies the mucosal alterations described in TM could be demonstrated. Thus TM is not specifically related to colorectal adenocarcinoma and probably arises as a secondary phenomenon. The claim that TM represents a premalignant change cannot be substantiated.